Detection of irradiated components in mixtures of herbs and spices by thermoluminescence - Sandeva, I; Spasevska, H; Ginovska, M; Stojanovska-Georgievska, L (Elsevier, 2020)
Treatment of food with ionizing radiation is used for reducing the number of harmful microorganisms and toxins, delaying ripening and preventing sprouting. A number of methods have been developed for detection of irradiated food. Photostimulated luminescence and thermoluminescence are physical methods for detection of irradiated food containing silicate minerals. Measurements for this study are done by photostimulated luminescence and thermoluminescence methods on mixtures of irradiated and unirradiated quartz and paprika samples. Examined samples containing irradiated components showed luminescence characteristics associated with irradiated minerals. Low content of irradiated material could still be detected by these methods, making them useful for detection of food containing irradiated ingredients.
Keywords: Thermoluminescence; Photostimulated luminescence; Irradiated food